Prototype of Landslide Disaster Early Warning System in Tomohon City Using Raspberry Pi - V Dotulong, Fernando; Pieters, Wesly Christian M.; Wondal, Priska Sembel; Senduk, Yohanes (JUKI : Jurnal Komputer dan Informatika, 2025)
Indonesia faces a high risk of landslides, particularly in areas with heavy rainfall and steep topography, such as Tomohon City in North Sulawesi. The area of Tomohon, especially the route between KM 12 and KM 17 in Tinoor 1 Village, is known for its landslide susceptibility, posing a constant threat to the safety of residents and road users. Therefore, a landslide early warning system (EWS) capable of providing real-time alerts is essential to help reduce the impact of such events. This research aims to develop a prototype EWS based on Raspberry Pi, equipped with tilt sensors and accelerometers to detect soil movement in landslide-prone areas in Tomohon City. Sensor data is collected and processed by the Raspberry Pi, with measurement results distributed via a web platform in real-time, enabling the community and authorities to respond promptly. This system demonstrates adequate detection capabilities and can contribute to landslide disaster mitigation efforts in Tomohon. The implementation of this prototype not only enhances technical disaster preparedness but also promotes community resilience through technology-based mitigation strategies. By integrating IoT devices with real-time data processing, the system provides a proactive solution that can significantly minimize casualties and infrastructure damage. Furthermore, the real-time accessibility of data through a web platform empowers both residents and local authorities to make informed decisions during emergencies. This research thus serves as a practical model for other regions in Indonesia with similar geographical conditions, reinforcing the importance of adopting innovative technologies in addressing the growing challenges of natural disasters.